The release of eosinophil chemotactic activity and eosinophil chemokinesis inhibitory activity by mononuclear cells from atopic asthmatic and non-atopic subjects. Issue 1 (2000) - Grzegorczyk, J.; Majkowska-Wojciechowska, B.; Kowalski, M. L.
Abstract : The goal of our study was to assess the chemotactic activity for eosinophils (ECA) and neutrophils (NCA) and histamine releasing activity (HRA) in crude supernatants of mononuclear cells in monosensitized atopic asthmatics and healthy controls. Chemotactic activity for ECA and neutrophils was measured in supernatants of cultured mononuclear cells with modified Boyden's chamber and HRA was assessed on healthy donor basophils. With respect to ECA generation two distinct subgroups of subjects were distinguished: releasers [ECA (+)] and non-releasers [ECA (–)]. In atopic and non-atopic ECA (+) the mean ECA index was 3.78 ± 0.49 and 2.47 ± 0.27 respectively ( P > 0.05). Supernatants from the remaining subjects (seven of 22 atopic and five of 11 non-atopic) did not express ECA, but revealed significant inhibitory activity for chemokinesis of eosinophils (mean chemotactic index 0.25 ± 0.16 and 0.48 ± 0.22 for atopic and non-atopic non-releasers respectively). Stimulation with antigen of MNC from atopic and with PHA from non-atopic ECA (–) restored cells ability to release ECA. Sephadex gel chromatography revealed that supernatants of MNC contained chemotactic and chemokinesis inhibitory activity in different fractions. The spontaneous productions of NCA and HRA by mononuclear cells was sim ilar in ECA releasers and non-releasers, although the HRA was higher following stimulation with PHA in the non-atopic ECA (+) subgroup. Our study demonstrated, for the first time, that MNC are capable of generating not only chemotactic activity but also chemokinesis inhibitory activity for eosinophils.